Are Adult Businesses Crime Hotspots? Comparing Adult Businesses to Other Locations in Three Cities. (9th March 2014) - Seaman, Christopher; Linz, Daniel
Abstract : This study addresses three questions pertinent to the debate concerning the secondary crime effects of adult businesses. (1) Are adult businesses hotspots for crime? (2) How do adult businesses compare with controls with regard to crime? (3) What subclasses of adult business are most likely to be associated with crime? A study of three cities reveals that adult businesses tended to fall outside the heaviest concentrations of criminal activity. Further, adult bookstores were less related to crime than both cabarets and on-site liquor-serving establishments. While adult cabarets were associated with ambient crime, crime was generally equivalent to nonadult liquor-serving establishments. A weighted intensity value analyses revealed that crime generally was more "intense" around liquor-serving establishments than around adult cabarets across the municipalities. These findings suggest that the relationship between cabarets and crime is not due to the presence of adult entertainment per se but rather due to the presence of liquor service. This finding is consistent with central precept of routine activities theory that areas that contain public establishments that serve alcohol facilitate crime.